Evaluation of Tamoxifen and metabolites by LC-MS/MS and HPLC Methods - Heath, D.D. (Br J Biomed Sci, 2014)
Epidemiological and laboratory evidence suggests that quantification of serum or plasma levels of tamoxifen and the metabolites of tamoxifen, 4-hydroxy-N-desmethyl-tamoxifen (endoxifen), Z-4-hydroxy-tamoxifen (4HT), N-desmethyl-tamoxifen (ND-tam) is a clinically useful tool in the assessment and monitoring of breast cancer status in patients taking adjuvant tamoxifen. A liquid chromatographic mass spectrometric method (LC-MS/MS) was used to measure the blood levels of tamoxifen and the metabolites of tamoxifen. This fully automated analytical method is specific, accurate and sensitive. The LC-MS/MS automated technique has now become a widely accepted reference method. We analyzed a randomly selected batch of blood samples from participants enrolled in a breast cancer study to compare results from this reference method in 40 samples with those obtained from a recently developed high performance liquid chromatography (HPLC) method with fluorescence detection. The mean (SD) concentration for the LC-MS/MS (endoxifen 12.6 [7.5] ng/mL, tamoxifen 105 [44] ng/mL, 4-HT 1.9 [1.0] ng/mL, ND-tam 181 [69] ng/mL) and the HPLC (endoxifen 13.1 [7.8] ng/mL, tamoxifen 108[55]ng/mL, 4-HT 1.8 [0.8] ng/mL, ND-tam 184 [81] ng/mL), the methods did not show any significant differences. Our results confirm that the HPLC method offers an accurate and comparable alternative for the quantification of tamoxifen and tamoxifen metabolites.